The curve is defined by `x = t - t^(-1)` and `y = 5 + t^2`

`dx/dt = 1 + 1/t^2`

`dy/dt = 2t`

`dy/dx = (dy/dt)/(dx/dt) = (2t)/(1 + 1/t^2)`

At the point where t = 1, `dy/dx = 2/2 = 1`

The slope of the...

## Unlock

This Answer NowStart your **48-hour free trial** to unlock this answer and thousands more. Enjoy eNotes ad-free and cancel anytime.

Already a member? Log in here.

The curve is defined by `x = t - t^(-1)` and `y = 5 + t^2`

`dx/dt = 1 + 1/t^2`

`dy/dt = 2t`

`dy/dx = (dy/dt)/(dx/dt) = (2t)/(1 + 1/t^2)`

At the point where t = 1, `dy/dx = 2/2 = 1`

The slope of the graph with respect to the value of t varies as shown in the following graph:

The tangent to the curve at the point where t = 1 has a slope of 1. The equation of the tangent is `(y - 6)/(x - 0) = 1`

=> y - 6 = x

=> x - y + 6 = 0

**The required equation of the tangent is x - y + 6 = 0**